2001
DOI: 10.1523/jneurosci.21-03-00875.2001
|View full text |Cite
|
Sign up to set email alerts
|

Golgi Complex, Endoplasmic Reticulum Exit Sites, and Microtubules in Skeletal Muscle Fibers Are Organized by Patterned Activity

Abstract: The Golgi complex of skeletal muscle fibers is made of thousands of dispersed elements. The distributions of these elements and of the microtubules they associate with differ in fast compared with slow and in innervated compared with denervated fibers. To investigate the role of muscle impulse activity, we denervated fast extensor digitorum longus (EDL) and slow soleus (SOL) muscles of adult rats and stimulated them directly with patterns that resemble the impulse patterns of normal fast EDL (25 pulses at 150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
75
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 43 publications
13
75
0
Order By: Relevance
“…Additionally, it is known that vesicular trafficking and organelle localization require proper microtubule function in muscle cells (20,54). Despite these insights into microtubule function, little is known about the relevance of microtubule tethering and lattice organization in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is known that vesicular trafficking and organelle localization require proper microtubule function in muscle cells (20,54). Despite these insights into microtubule function, little is known about the relevance of microtubule tethering and lattice organization in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…As an unexpected novel finding of this study, this difference suggests that different levels of electrical stimulation might be an important factor for controlling the expression of tubulin and that α-tubulin is potentially controlled by neuronal stimulation. Ralston et al (29) reported that different frequencies of electrical stimulation induced different densities and orientations of microtubules in the soleus (which dominantly has MHC I) and extensor digitorum longus (which dominantly has MHC II) muscles, whereby 150 Hz (100 Hz in this study) stimulation applied to the fast muscle preserved the pattern/quantity of microtubules; however, microtubules in the slow muscle under the same stimulation showed thinner and were fewer in quantity. We have hypothesized that a decrease in the pool of tubulin dimers rather than a decrease in microtubules is caused by higher frequencies of electrical stimulation comparing with the lower ones.…”
Section: Discussionmentioning
confidence: 46%
“…For MHC isoforms in slow and fast muscles, their isoform transitions show the following order MHC I↔MHC IIa↔MHC IId/x↔MHC IIb (9). Ralston et al (29) reported that 20 Hz stimulation induced a slow type I pattern in extensor digitorum longus fibers (fast) muscle, but stimulation with 150 Hz only partially succeeded in inducing a type II pattern in the soleus (slow) muscle. The difference in frequency of electrical stimulation (100 Hz of EIEC used in this study and 150 Hz of EIEC used in Ralston et al's study) might be responsible for the different results in this study compared with those of Ralston et al (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations